The epidemiology of post-traumatic stress disorder in Norway: trauma characteristics and pre-existing psychiatric disorders - Lassemo, Eva (Soc Psychiatry Psychiatr Epidemiol, 2016)
PURPOSE: The prevalence of PTSD differs by gender. Pre-existing psychiatric disorders and different traumas experienced by men and women may explain this. The aims of this study were to assess (1) incidence and prevalence of exposure to traumatic events and PTSD, (2) the effect of pre-existing psychiatric disorders prior to trauma on the risk for PTSD, and (3) the effect the characteristics of trauma have on the risk for PTSD. All stratified by gender. METHOD: CIDI was used to obtain diagnoses at the interview stage and retrospectively for the general population N = 1634. RESULTS: The incidence for trauma was 466 and 641 per 100,000 PYs for women and men, respectively. The incidence of PTSD was 88 and 31 per 100,000 PYs. Twelve month and lifetime prevalence of PTSD was 1.7 and 4.3 %, respectively, for women, and 1.0 and 1.4 %, respectively, for men. Pre-existing psychiatric disorders were risk factors for PTSD, but only in women. Premeditated traumas were more harmful. CONCLUSION: Gender differences were observed regarding traumatic exposure and in the nature of traumas experienced and incidences of PTSD. Men experienced more traumas and less PTSD. Pre-existing psychiatric disorders were found to be risk factors for subsequent PTSD in women. However, while trauma happens to most, it only rarely leads to PTSD, and the most harmful traumas were premeditated ones. Primary prevention of PTSD is thus feasible, although secondary preventive efforts should be gender-specific.